1975
DOI: 10.1002/jcp.1040850409
|View full text |Cite
|
Sign up to set email alerts
|

Use of mutant fibroblasts in the analysis of the regulation of cholesterol metabolism in human cells

Abstract: Analysis of mutant human fibroblasts deficient in a cell surface receptor for low density lipoproteins (LDL) has led to the delineation of an important, hitherto unrecognized, regulatory process for cholesterol metabolism. On normal cells, binding of LDL to this receptor regulates cholesterol metabolism by two mechanisms: (a) suppression of cholesterol synthesis and (b) facilitation of the rate of proteolytic degradation of the lipoprotein. In cells from homozygotes with the autosomal dominant disorder Familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…DISCUSSION The mutant cells studied here show a marked defect in feedback inhibition of cholesterol synthesis by LDL, a marked defect in degradation of the apoprotein moiety of LDL, and a marked decrease in the total cell-associated 125I-LDL after incubation at 37°. These findings agree with those of Brown, Goldstein, and coworkers in fibroblasts of other HFH patients (4). When, however, cell-associated radioactivity was After overnight incubation in lipoprotein-deficient medium, the cells were chilled on ice for 15 min, fresh lipoprotein-deficient medium and 125j-LDL were added, and incubation was continued for 2 hr at 00.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…DISCUSSION The mutant cells studied here show a marked defect in feedback inhibition of cholesterol synthesis by LDL, a marked defect in degradation of the apoprotein moiety of LDL, and a marked decrease in the total cell-associated 125I-LDL after incubation at 37°. These findings agree with those of Brown, Goldstein, and coworkers in fibroblasts of other HFH patients (4). When, however, cell-associated radioactivity was After overnight incubation in lipoprotein-deficient medium, the cells were chilled on ice for 15 min, fresh lipoprotein-deficient medium and 125j-LDL were added, and incubation was continued for 2 hr at 00.…”
supporting
confidence: 91%
“…Although this is always less than the amount degraded by the normal cells at the same high concentration, it can be comparable to that degraded by normal cells at low LDL concentrations, yet there is not accompanying inhibition of sterol synthesis. Either one must postulate that interaction with specific receptors on the membrane is a necessary component of the control mechanism as suggested by Brown, Goldstein et al (4,15) or, alternatively, that the fate of LDL entering the mutant cells is different in some fashion, as suggested by the present result showing an apparently greater fractional degradation ( Table 2). …”
mentioning
confidence: 66%
“…In 1973 Beg and coworkers reported that a microsomal preparation of rat liver 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA reductase), a key regulatory enzyme of cholesterol biosynthesis, was inactivated in a time-dependent manner by incubation with MgATP and a cytosolic fraction (1). The same phenomenon was observed in microsomes from human fibroblasts, where evidence was presented that both ADP and ATP were required (5). The apparent requirement for ADP was almost certainly because AMP was being generated from it via the adenylate kinase reaction.…”
Section: Early History Of Mammalian Amp-activated Protein Kinasementioning
confidence: 87%
“…On the other hand, the suppression of HMG-CoA reductase activity in cells grown in the presence of serum or serum lipoproteins was assumed by Brown and Goldstein (6,7) and by Kirsten and Watson (8) to be due to the cholesterol component of the lipoproteins. Weak suppression of HMG-CoA reductase activity in fibroblast cultures by relatively high levels of nonlipoprotein cholesterol has also been reported from several laboratories (1,(9)(10)(11).…”
mentioning
confidence: 55%